2D multichannel seismic reflection raw data of RV SONNE during cruise SO301 - Engels, Martin; Schnabel, Michael; Ehrhardt, Axel; Berndt, Janine (PANGAEA, 2025)
The raw 2D multichannel seismic reflection data presented in this project were acquired during expedition SO301 north of the Rodrigues Triple Junction. Data collection targeted the Central Indian Ridge, including the 25°S Oceanic Core Complex (OCC) and the Kairei hydrothermal field, to investigate crustal structure and faulting processes at a slow spreading ridge. A total of 29 seismic lines were recorded using an 8 km, 756-channel streamer and an air gun source array. The dataset covers approximately 1871 line kilometers and includes profiles across ridge segments, the OCC, and conjugate flanks. The data are provided in raw SEG-D format with associated navigation and standardized metadata. Detailed information on the acquisition can be found in the SO301 cruise report (https://doi.org/10.48433/cr_so301). In addition, a technical report is provided with this data set.
Keywords: 2D seismic data; crustal strcuture; earthquake; GGun array; hydrothermal field; multi-channel seismic reflection; oceanic core complex; raw data; slow spreading